'It makes you someone who changes with the times': health worker and client perspectives on a smartphone-based counselling application deployed in rural Tanzania. Issue 4 (1st June 2019) - Hackett, Kristy; Kazemi, Mina; Lafleur, Curtis; Nyella, Peter; Godfrey, Lawelu; Sellen, Daniel
Abstract: Mobile health (mHealth) applications have been developed for community health workers (CHW) to help simplify tasks, enhance service delivery and promote healthy behaviours. These strategies hold promise, particularly for support of pregnancy and childbirth in low-income countries (LIC), but their design and implementation must incorporate CHW clients' perspectives to be effective and sustainable. Few studies examine how mHealth influences client and supervisor perceptions of CHW performance and quality of care in LIC. This study was embedded within a larger cluster-randomized, community intervention trial in Singida, Tanzania. CHW in intervention areas were trained to use a smartphone application designed to improve data management, patient tracking and delivery of health messages during prenatal counselling visits with women clients. Qualitative data collected through focus groups and in-depth interviews illustrated mostly positive perceptions of smartphone-assisted counselling among clients and supervisors including: increased quality of care; and improved communication, efficiency and data management. Clients also associated smartphone-assisted counselling with overall health system improvements even though the functions of the smartphones were not well understood. Smartphones were thought to signify modern, up-to-date biomedical information deemed highly desirable during pregnancy and childbirth in this context. In this rural Tanzanian setting, mHealth tools positively influenced community perceptions of health system services and client expectations of health workers; policymakers and implementers must ensure these expectations are met. Such interventions must be deeply embedded into health systems to have long-term impacts on maternal and newborn health outcomes.